Investigation of the Compressive Strength of CFRP Wrapped Nylon Fiber Reinforced Concrete Cylinders (Journal of Engineering Science, 2022)
Nylon fibers are found to increase the mechanical properties of structural concrete like compressive and tensile strength when introduced into the concrete matrix by partially replacing fine aggregates. Since Nylon fibers are cheap waste materials, properly controlling their percentage into the matrix results in higher strength as well as cost control. This study discusses the compressive strength of nylon fiber induced concrete cylinders by wrapping them with 200gsm carbon fiber sheets as well as records the failure pattern, which is done by comparing the compressive strength of control specimens with sets of cylinders which are induced with nylon fiber and wrapped around with zero, one and three layers of CFRP laminates. Alongside the compressive test results, this study also reflects on several tensile tests carried out on CFRP strips which can be used as a measure to check hardener bond strengths in field. For that purpose, five coupons were prepared for flat tensile test and another five for overlap splice tensile test, stress-strain data were recorded; and the tests followed the guidelines stated in ACI code. The recorded tensile test data was found satisfactory with the recommended values for ACI 440.3R-04 and better compression capacity for cylinders were found with increasing CFRP layers.Journal of Engineering Science 13(1), 2022, 31-39